Answer:
-3/2 ±1/2 sqrt(5) = x
Explanation:
f(x) = 2x^2 + 6x + 2
Set the function equal to 0
0 = 2x^2 + 6x + 2
Factor out 2
0 = 2(x^2 + 3x + 1)
Divide by 2
0 = (x^2 + 3x + 1)
Subtract 1 from each side
-1 = x^2 +3x
Complete the square by dividing the x coefficient by 2 and then squaring
(3/2)^2 = 9/4
-1 +9/4 = x^2 +3x+9/4
-4/4+9/4 = (x+3/2) ^2
5/4 = (x+3/2) ^2
Taking the square root of each side
± sqrt(5/4) = sqrt( (x+3/2) ^2)
±1/2 sqrt(5) = (x+3/2)
Subtract 3/2 from each side
-3/2 ±1/2 sqrt(5) = x